A novel fluorescent probe for ratiometric detection of formaldehyde in real food samples, living tissues and zebrafish. (30th November 2020) - Yuan, Gangqiang; Ding, Haiyuan; Peng, Longpeng; Zhou, Liyi; Lin, Qinlu
Highlights: Design and synthesis of a new TP-FRET-based ratiometric fluorescent probe for detecting FA. The ratiometric probe responses to FA rapidly with high selectivity and sensitivity during 65 s. The probe has a good imaging resolution and depth of deep tissue penetration in real samples. Abstract: Herein, a two-photon (TP) ratiometric fluorescent probe (NpFA ) was developed for detecting formaldehyde (FA) in real food samples, living onion tissues and zebrafish by fluorescence resonance energy transfer (FRET) strategy. Specifically, a TP fluorophore as the donor and a FA turn-on naphthalimide fluorophore as the acceptor were connected by a non-conjugated linker to construct the TP-FRET-based NpFA, which exhibited a target-modulated ratiometric fluorescence response to FA rapidly with high selectivity and sensitivity during 65 s, and a large ratio ~5-fold enhancement at I550 /I410 after addition of FA, displaying ~60-fold enhancement at 550 nm and a quite low DOC of 5.8 ± 0.2 nM. Moreover, NpFA has a good imaging resolution and depth of deep tissue penetration. Therefore, based on the above results, NpFA has the capability to be a useful tool for investigating FA in real samples application, and we also hope NpFA will further study of the physiological and pathological function of FA.